Potencial do uso do líquido da casca do coco verde na cultura do Coqueiro-anão - Andrade, Hosana Aguiar Freitas de (2021)
The use of green coconut by-products as a raw material for the industry generates green coconut shell liquid (LCCV), an effluent that has potential for use in agriculture as a source of potassium, the main nutrient required by the dwarf coconut tree. However, LCCV has a high tannin content, which can inhibit the mineralization of organic nitrogen. The objective was to evaluate the potential use of green coconut shell liquid in the cultivation of young dwarf coconut plants and its impact on nitrogen mineralization. The research was divided into two parts: I) Potted experiment, conducted in a completely randomized design, consisting of five replications and seven treatments, with five doses: 0% (L0), 50% (L50), 100% (L100), 150% (L150) and 200% (L200) of the need for K2O in the form of LCCV; and two additional treatments: 100% in the form of KCl (K100) and 50% in the form of KCl and 50% of LCCV (L50 + K50). The treatments were over three months. One hundred and twenty days after transplanting the seedlings, the chemical attributes of the soil, growth and nutritional status of the dwarf coconut tree were taken. II) Laboratory experiment, carried out to evaluate the mineralization of organic N from the soil in a completely randomized design, with a 4 x 9 factorial scheme, and three replications. Four treatments were taken (L0, L100, L200 and K100) and 9 evaluation times (on the day of application of treatments to the soil and at 7; 15; 30; 60; 90; 120; 150 and 180 days of incubation). As doses of LCCV promoted increases in organic matter, K+, Mg2+, Na+, Cu2+ and Fe2+, and a decrease in P, Ca2+ and Mn2+ in the soil and a decrease in the% of live leaves of the dwarf coconut tree. The doses L100 and L200 affected the mineralization of organic nitrogen in the soil due to the presence of tannins, the high concentration of salts and the high C:N ratio (150:1) without effluent. The dose L100, compared to K100, increased the concentration of K+ and the electrical conductivity of the soil and decreased the % of live leaves, as absolute and relative growth rates of the stem, and as dry masses of leaves, stem and total. The treatment L50 + K50 showed no difference in relation to K100 for growth variables, except for the % of live leaves, indicating the possibility of replacing 50% of the recommended dose of K2O for the cultivation of dwarf coconut by LCCV